Psychology Policing. - Ainsworth, Peter (Taylor and Francis, 2012)
Applied psychology has become increasingly important in the work of policing, police training and the academic study of policing. This book provides a highly accessible account of the way in which psychological principles and practices are applied to policing, reflecting the increasing attention being given to this area in the light of recent concerns about police training and its effectiveness - for example the MacPherson report. The book sets out the main areas of applied psychology which have particular relevance for policing, looking at how these impact in practice on police work - retriev.